In-migration to irish cities and towns, 1970-71 - Hourihan, K (Economic & Social Studies, 1982)
Precis: Cities and towns played an important role in internal migration and immigration in Ireland in 1970-71. Gross migration rates were strongly related to estimates of the employment increases in the centres over the year. Canonical correlation analysis shows that the migration process comprised a "general" trend and three specialised aspects. These were related to different characteristics of the cities and towns and to employment increase by industrial sector.
Keywords: Economics; Sociology